Kombinasi Pemupukan Organik dan Anorganik Terhadap Laju Pertumbuhan dan Rasio Bobot Basah Tajuk Akar Tanaman Padi Sawah (Oryza sativa L.) - Siti Aminah; Muhammad Afrillah; Oviana Lisa; Muhammad Reza Aulia (Universitas Teuku Umar, 2023)
Rice as one of the main food sources for the Indonesian people, especially North Sumatra, is still not able to meet the needs even though it has large land potential, so it is necessary to increase production through fertilization. This study aims to determine the effect of a combination of organic and inorganic fertilization on the growth of paddy rice plants. This study used a factorial randomized block design consisting of three factors, namely KCL (K) at 4 dose levels, namely K0 (0 kg/ha), K1 (25 kg/ha), K2 (50 kg/ha) and K3 (75 kg/ha). ), Urea (U) two levels namely U1(250 kg/ha) and U2 (225 kg/ha), Straw Compost (J) 2 levels namely J0 (0 tons/ha) and J1 (5 tons/ha) with a total The treatment combinations were 16 and consisted of 3 replications and 48 samples. Held in the rain-fed rice field area of Clove Turi sub-district, Binjai City. Soil sample analysis was carried out at the Analytical Laboratory of PT. Socfin Indonesia (SOCFINDO), Medan City and the Research and Technology Laboratory, Faculty of Agriculture, University of North Sumatra. The combination of inorganic and organic fertilizer treatments consisting of Potassium, Urea and Straw Compost showed no significant effect on the observed parameters of plant growth rate (cm/week) and root canopy wet weight ratio (grams). The highest plant growth rate was shown by the interaction of the three treatments, namely K3U2J0 of 10.33 cm/week, while the lowest data was shown by the interaction of the three treatments, namely K1U2J0 of 8.87 cm/week. The highest root canopy wet weight ratio was shown by the interaction of the three treatments, namely K1U1J0 of 8.69 grams while the lowest data was shown by the interaction of the two treatments between potassium and straw compost, namely K2J0 of 5.01 grams.Keywords: Fertilizer; Organic; Inorganic; Growth; Paddy